EFFECT WORD OF MOUTH, SERVICESCAPE, AND SERVICE QUALITY AND CONVENIENCE ON LOYALTY THROUGH TRUST AND PERCEIVED VALUE - Safitri, Fikta Novia Ayu; Sudirman, Hudyah Astuti; Satryawati, Satryawati; Anggraeni S., Fauziah Lily (Universitas Muhammadiyah Kalimantan Timur, 2024)
This study aims to analyze the influence of word of mouth, servicescape, service quality, and convenience towards Loyalty through Trust and Perceived Value for Happy Puppy Karaoke visitors in Samarinda. This study used a quantitative approach using path analysis which was processed with SPSS Statistic 23 software and Structural Equation Modeling (SEM) with IBM AMOS 23 software. The sample used in this study consisted of 162 samples taken from Happy Puppy Karaoke visitors in Samarinda City. In this study, instrument tests were carried out which consisted of validity and reliability tests, assumption tests using estimation tests, and structural model fit tests. Based on the structural model, it can be proven that Word of Mouth has no significant effect on Trust. Servicescape and Service Quality and Convenience have a significant effect on Trust. Word of Mouth, Servicescape, and Service Quality and Convenience significantly affect Perceived Value. Word of Mouth, Servicescape, and Service Quality and Convenience have no significant effect on Loyalty. Trust has no significant effect on Loyalty. Perceived Value has a significant effect on Loyalty for Happy Puppy Karaoke visitors in Samarinda.